PENGARUH KOMITMEN ORGANISASI, PERAN PENGELOLA KEUANGAN DAERAH, PARTISIPASI ANGGARAN, DAN AKUNTABILITAS PUBLIK TERHADAP KINERJA PIMPINAN SATUAN KERJA PERANGKAT DAERAH KOTA PAYAKUMBUH - Octalia, Roza; Rasuli, Muhammad; Diyanto, Volta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine the Influence of Organizational Commitment, Role of Regional Financial Management, Budget and Public Accountability Participation on Performance Leadership. The object of this study conducted at SKPD Payakumbuh, consisting of 25 SKPD. The population of this study was a leader who works at SKPD Payakumbuh. Selection of the sample in this study was based on a purposive sampling method. Respondents in this study were the Head SKPD, Secretary of SKPD, Head of Sub Division of Finance, Head of Sub Division of Administration. The Method of collecting primary data was survey techniques and giving the questions to the respondents by questionnaires. From 100 questionnaires sent, there were 94 respondents who returned the questionnaire and which can be processed and analyzed. The processing and analysis of data were using multiple linear regression analysis with SPSS (Statistical Product and Service Solution) version 17. The results showed that organizational commitment had a significant effect on the performance of the leadership, the role of regional financial managers had a significant effect on the performance of the leadership, the participation had a significant effect on the budget performance management, and public accountability also had a significant effect on the performance of the leadership.Keywords: Commitment, Role of Regional, Participation, Accountability, and Performance